INFORMATION LEGAL POLICY IN THE MODERN SOCIETY: COMPARATIVE ANALYSIS - Oksana Leonidovna Soldatkina; Aleksandr Vasil'evich Mal'ko (Сравнительная политика, 2018)
this article contains a comparative analysis of the main directions of the information policy of different states in three areas: information rights and freedoms, e-government and information security. Such a comparison is an actual character because the problems of information law are often global, and the legal regulation of information relations has an international component. Based on the results of the comparison of national legislations of different countries conducted in the article on certain issues of the information law, the following conclusions are made. Realization of the basic rights and freedoms of citizens in the information sphere occupies a special place among the national interests of most countries, but the rights of the individual can be limited. Legal restrictions in the information field are considered on the example of comparison of methods of content management of the global network, which are characterized by the state's definition of the level of interference in the network life of citizens and methods of ensuring intervention. Electronic governance in various states is characterized by a transition from the concept of "e-government" to the "digital government" model associated with the transformation of the entire structure of public administration. In this field, the UK experience is valuable, where the "Government as a platform" project is being implemented, and Germany, where the construction of "e-government" basically began with the enhancement of the information culture of citizens and civil servants. Information security today come out on top in the majority of countries and international organizations. In general, information security trends in all countries are similar, which is reflected in the Russian strategic documents.